The impact of compensation on corporate performance: The role of firm size and leverage - Afridayanti Surbakti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
This study aims to analyze the effect of compensation on company performance, focusing on the moderating role of company size and leverage. This study uses a sample of 300 companies listed in Indonesia from 2019–2021. The Ordinary Least Squares (OLS) method tests the relationship between variables. The results of the study indicate that increasing compensation significantly decreases company performance. This decline in performance is caused by ineffective compensation design and information asymmetry, which hinders management in achieving company targets. In addition, company size is found to moderate this relationship positively, where large companies tend to be able to design more effective compensation structures, thereby improving performance. Conversely, high leverage exacerbates the negative impact of compensation on performance, as it increases financial pressure and limits management flexibility in strategic decision-making. This study provides a theoretical contribution by emphasizing the importance of strategic and adaptive compensation design to the company's internal and external conditions. From a practical perspective, these findings guide company managers, especially in emerging markets such as Indonesia, to design optimal compensation structures to support sustainable growth and increase shareholder value.